MAKROZOOBENTHOS COMMUNITY STRUCTURE IN THE INTERTIDAL ZONE OF THE ISLAND OF SUBSTANCE OF BUNGUS DISTRICT CITY PADANG WEST SUMATERA PROVINCE - Junika Cecelia Putri; Afrizal Tanjung; Efriyeldi Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractMacrozoobenthos is a living organism that is relatively sedentary (sessile) and has varying adaptability to environmental conditions. In addition, macrozobenthos is also widely used as an indicator of pollution. This research was conducted in the waters of Pasumpahan Island, Bungus Subdistrict, Padang City, West Sumatera Province in April 2018, aiming to know macrozoobenthos community structure which includes: type, abundance, index of species diversity, uniformity index, dominance index and distribution pattern. Sampling using line transect method is done on 3 stations. The results of the study found 4 classes of macrozoobenthos with 9 species, where the value of macrozoobenthos abundance obtained ranged from 3.22 to 3.78 ind/m2. The index value of diversity of species ranged from 0.40 to 0.57 is relatively low, while the value of uniformity index ranged from 0.12 to 0.19 is not balanced, the value of the dominance index ranged from 0.12 to 0.18 ie no species which dominates and the value of the distribution pattern ranges from 3.21 to 5.09 with the pattern of distribution in groups.Keywords: Makrozoobenthos, Intertidal Zone, Pasumpahan Island, Community Structure